(untitled) (American Journal of Islam and Society, 2016)
In his review of Maha Elkaisy-Friemuth’s Gods and Humans in Islamic Thought: Abdul-Jabbār, Ibn Sīna and al-Ghazāli (Abingdon: Routledge, 2006), Sajjad Rizvi (2008) identifies three paths proposed by three influential medieval thinkers as characterizing the interconnected nature of intellectual inquiry in Islam: Abd al-Jabbar (d. 1025), regarded as representing the kalām tradition, Ibn Sina (d. 1037) of the philosophical orientation, and al-Ghazali (d. 1111) of the Sufi tradition. If Rizvi had accurately added the juridical or jurisprudential dimension to Elkaisy-Friemuth’s perspective, his review would have panoramically captured the essence of Islam’s intellectual tradition. The elegant book under review, Iftā and Fatwa in the Muslim World and the West, edited by Zulfiqar Ali Shah, has taken care of that major omission in what may be described as a virtually all-encompassing look at emerging concerns in iftā’ (formulating a fatwa) and fatwa (issuing a fatwa). The book features an introduction by the editor and eight chapters by scholars in the various foci of the subject covered. The introduction situates the book’s subject in a historical context and exposes its indebtedness to the seminar convened during July 2011 by the International Institute of Islamic Thought’s (IIIT) Summer Institute for Scholars, which addressed this topic. The editor attributes the emergence of consensus on the chaotic nature of the contemporary processes of both iftā’ and fatwa to the seminar. He then identifies the intellectual skills required for analytical reasoning, as well as the broad general knowledge of the fields relevant to the cultural contexts of their verdicts, as the strength that characterized the excellent performance of scholars in fatwa formulation and issuance from the rise of the Abbasids in 750 to the fall of Andalusia in 1492. Conversely, contemporary knowledge is fragmented into specializations and sub-specializations, all of which can hardly be mastered by one scholar or group of scholars. The editor, who engages critically with various issues and concerns involved in the contemporary formulation and issuance of fatwa, also provides a brief description of each chapter’s subject. However, the word al-fiqh al-istidlālī (demonstrative fiqh) is wrongly rendered as fiqh alistighlālī (p. 10) ...